Studies on Effect of Light Source on the Stability and In Vitro Antioxidant Activity of Dyes and Extracts from Annatto (Bixa orellana L.) Seed - Pamidighantam, Prabhakara Rao (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
Isolation of the oleoresin, total lipid, hexane soluble matter (fat), bixin powder and norbixin formulation from annatto (Bixa orellana.L) seed was carried out and the effect of exposure to natural sun light and artificial incandescent light on the stability of bixin, norbixin and their solutions was evaluated. The results could be correlated with data on in-vitro antioxidant activity of the extracts by Ferric reducing power and ABTS assays. Solvent extraction of annatto seed by different methodologies yielded by oleoresin (6.1%), total lipid (5.93%), oil (3.0%) and a natural red dye (1.2%). The stability was higher in dye powders than in solutions when exposed to artificial incandescent light or sunlight. The order of activity as determined by ferric reducing power was, seed oil > oleoresin> total lipid> norbixin> bixin. However, the order of antioxidant activity according to ABTS assay was oleoresin > seed oil > norbixin > total lipid > bixin.Â Keywords: bixin, norbixin, annatto extracts, effect of light, antioxidant activity, ferric reducing power, ABTS assay